Organ‐on‐a‐Chip: A Preclinical Microfluidic Platform for the Progress of Nanomedicine. Issue 51 (25th November 2020) - Rodrigues, Raquel O.; Sousa, Patrícia C.; Gaspar, João; Bañobre‐López, Manuel; Lima, Rui; Minas, Graça
Abstract: Despite the progress achieved in nanomedicine during the last decade, the translation of new nanotechnology‐based therapeutic systems into clinical applications has been slow, especially due to the lack of robust preclinical tissue culture platforms able to mimic the in vivo conditions found in the human body and to predict the performance and biotoxicity of the developed nanomaterials. Organ‐on‐a‐chip (OoC) platforms are novel microfluidic tools that mimic complex human organ functions at the microscale level. These integrated microfluidic networks, with 3D tissue engineered models, have been shown high potential to reduce the discrepancies between the results derived from preclinical and clinical trials. However, there are many challenges that still need to be addressed, such as the integration of biosensor modules for long‐time monitoring of different physicochemical and biochemical parameters. In this review, recent advances on OoC platforms, particularly on the preclinical validation of nanomaterials designed for cancer, as well as the current challenges and possible future directions for an end‐use perspective are discussed. Abstract : This review presents the recent advances on organ‐on‐a‐chip platforms for the preclinical validation of nanomaterials designed for medicine. The current challenges, such as the integration of biosensor modules for long‐time monitoring of different physicochemical and biochemical parameters, and future directions for an end‐use perspective are highlighted. The TOC image was created with BioRender.com.